Surface‐Plasmon‐Enhanced Transmetalation between Copper and Palladium Nanoparticle Catalyst. (20th April 2022) - Liu, Xin; Shi, Yujian; Jin, Yichao; Tana, Tana; Peiris, Erandi; Zhang, Xueming; Xu, Feng; Waclawik, Eric R.; Bottle, Steven E.; Zhu, Huaiyong; Sarina, Sarina
Abstract: Surface‐plasmon‐mediated phenylacetylide intermediate transfer from the Cu to the Pd surface affords a novel mechanism for transmetalation, enabling wavelength‐tunable cross‐coupling and homo‐coupling reaction pathway control. C−C bond forming Sonogashira coupling and Glaser coupling reactions in O2 atmosphere are efficiently driven by visible light over heterogeneous Cu and Pd nanoparticles as a mixed catalyst without base or other additives. The reaction pathway can be controlled by switching the excitation wavelength. Shorter wavelengths (400–500 nm) give the Glaser homo‐coupling diyne, whereas longer wavelength irradiation (500–940 nm) significantly increases the degree of cross‐coupling Sonogashira coupling products. The ratio of the activated intermediates of alkyne to the iodobenzene is wavelength dependent and this regulates transmetalation. This wavelength‐tunable reaction pathway is a novel way to optimize the product selectivity in important organic syntheses. Abstract : The localized surface plasmon resonance effect of Cu nanoparticles enhances transmetalation and phenylacetylide intermediate transfer from the Cu surface to the Pd surface by low‐flux visible light. This feature enables a choice between the cross‐coupling product and homo‐coupling product dependent on wavelength.